Biomarkers of the intake of dietary polyphenols: strengths, limitations and application in nutrition research - Spencer, Jeremy P. E.; Abd El Mohsen, Manal M.; Minihane, Ann-Marie; Mathers, John C. (British journal of nutrition, 2008)
In order to establish firm evidence for the health effects of dietary polyphenol consumption, it is essential to have quantitative information regarding their dietary intake. The usefulness of the current methods, which rely mainly on the assessment of polyphenol intake using food records and food composition tables, is limited as they fail to assess total intake accurately. This review highlights the problems associated with such methods with regard to polyphenol-intake predictions. We suggest that the development of biological biomarkers, measured in both blood and urine, are essential for making accurate estimates of polyphenol intake. However, the relationship between dietary intakes and nutritional biomarkers are often highly complex. This review identifies the criteria that must be considered in the development of such biomarkers. In addition, we provide an assessment of the limited number of potential biomarkers of polyphenol intake currently available.